Identification of the Key Pathways and Genes in Hypoxia Pulmonary Arterial Hypertension Following Intrauterine Growth Retardation - Zhu, Weifen; Zhang, Ziming; Gui, Weiwei; Shen, Zheng; Chen, Yixin; Yin, Xueyao; Liang, Li; Li, Lin (Frontiers in Molecular Biosciences, 2022)
High-throughput sequencing and weighted gene co-expression network analysis (WGCNA) were used to identify susceptibility modules and genes in liver tissue for the hypoxic pulmonary arterial hypertension (PAH) animal model following intrauterine growth retardation (IUGR). A total of 5000 genes were clustered into 8 co-expression modules via WGCNA analysis. Module blue was mostly significantly correlated with IUGR-hypoxia group. The Gene Ontology analysis showed that genes in the module blue were mainly enriched in fatty acid metabolic process, lipid modification and fatty acid catabolic process. The Kyoto Encyclopedia of genes and Genomes enrichment analyses showed that the genes in module blue were mainly associated with fatty acid metabolism, PPAR signaling pathway, and biosynthesis of unsaturated fatty acids. In addition, the Maximal Clique Centrality method was used to identify the hub genes in the sub-networks and the obtained results were verified using real time quantitative PCR. Finally, we identified that four genes including Cyp2f4, Lipc, Acadl and Hacl1 were significantly associated with IUGR-hypoxia. Our study identified a module and several key genes that acted as essential components in the etiology of the long-term metabolic consequences in hypoxia PAH following IUGR.